Adolescent girls' and parents' views on recruiting and retaining girls into an after-school dance intervention: implications for extra-curricular physical activity provision - Powell Jane; Haase Anne; Sebire Simon J; McNeill Jade; Davis Laura; Jago Russell; Cooper Ashley R (BMC, 2011)
Abstract Background Many adolescents are not sufficiently active and girls are less active than boys. Physical activity interventions delivered during curriculum time have reported weak effects. More sustained changes in physical activity may be obtained by facilitating participation in enjoyable activities. Dance is the favourite activity of UK girls but there is a shortage of dance provision. Dance sessions delivered after the school day could prove to be an effective means of engaging adolescent girls in physical activity. There is a lack of information about the factors that would affect girls' recruitment and retention in an after-school dance programme. Methods Focus groups were conducted with 65, Year 7 (11-12 year old) girls from 4 secondary schools in Bristol. In-depth phone interviews were also conducted with 16 (4 per school) of the girls' parents. Interviews and focus groups examined issues that would affect recruitment into the intervention, strategies that could be used to attract girls who have little or no previous experience in dance, any factors that would increase their interest in participating in an after-school dance programme and any factors that would affect retention in the programme. All interviews and focus groups were digitally recorded and thematically analysed. Results Girls reported that a taster session in which they had an opportunity to sample the intervention content and "word of mouth" campaigns by peers, who did not need to be their friends, would encourage them to participate in an after-school dance programme. Sessions that maximised enjoyment and facilitated socialisation opportunities would enhance retention. Parents reported that encouraging groups of friends to join the programme, and stressing the enjoyment of the session would increase participation. Conclusions Recruitment and retention campaigns that focus on enjoyment, socialisation, mastery, goal setting and relating to other girls may be effective strategies for recruiting and retaining girls in an after-school dance programme. These factors are consistent with well-established theories of individual behaviour change such as self-determination theory and social cognitive theory. Recruitment and retention campaigns that are targeted to address theoretically derived mediators of behaviour may be more effective than traditional approaches.